Comparison of the shock absorption capacities of different mouthguards - Bochnig, Melina Simonetta; Oh, Min‐Jung; Nagel, Theresa; Ziegler, Fred; Jost‐Brinkmann, Paul‐Georg (Dental traumatology, 2017)
Background/Aims In this in vitro study, the protective qualities of different mouthguard types were examined during small hard object collisions. The aim was to investigate inconclusive aspects of hard inserts, nylon nets, and air spaces as reinforcements in the anterior region and the protection qualities of ethylene vinyl acetate (EVA). Materials and Methods Five different mouthguards with a labial thickness between 2 mm and 11 mm made of materials of varying stiffness were investigated. As a negative control, the same experiments were performed without a mouthguard. Different combinations of EVA and labial inserts ((polyethylene terephthalate glycol‐modified [PETG]), nylon mesh, air space) were tested. Using a stainless steel pendulum device, blows of different energy (0.07‐2.85 joules) were applied to the center of the crown of a pivoted tooth in a custom‐built jaw model. A laser Doppler vibrometer measured the tooth deflection, while an acceleration sensor attached to the pendulum measured the braking accelerations. Results Tooth deflection was reduced up to 99.7% compared to no mouthguard, and the braking acceleration was reduced up to 72.2% by increasing the mouthguards' labial thickness in combination with labial inserts of different stiffness and a built‐in air space between the front teeth and the mouthguard. The mouthguards made of soft materials (EVA with nylon mesh) showed slightly better protection qualities than the more rigid mouthguards of similar thickness (PETG; P<.05). However, with increasing impact energy, their protective capacities decreased to a greater extent than the stiffer mouthguards. Conclusions The combination of increased labial thickness and labial inserts of varying stiffness and eventually an air space offers the best protection capacities for hard, small object collisions.